2014
DOI: 10.1371/journal.pone.0113625
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Postural Tachycardia Syndrome in Children and Adolescents

Abstract: BackgroundPostural tachycardia syndrome (POTS) is prevalent in children and adolescents and has a great impact on health. But its risk factors have not been fully understood. This study aimed to explore possible risk factors for children and adolescents with POTS.Methods and Findings600 children and adolescents (test group) aged 7–18 (11.9±3.0) years old, 259 males and 341 females, were recruited for identifying its risk factors. Another 197 subjects aged from 7 to 18 (11.3±2.3) years old were enrolled in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 33 publications
(34 reference statements)
0
41
0
1
Order By: Relevance
“…106 Sleep disorders, such as problematic sleep onset, maintenance, duration, quality, and daytime sleepiness, are consistently reported. 5,53,57,107,108 However, sleep studies in adults have shown little differences in sleep characteristics among POTS patients and controls. 109 -112 Cognitive symptoms or brain fog, which is described as having difficulty with attention, concentration, and memory, are commonly reported in POTS.…”
Section: Immune Mechanismsmentioning
confidence: 99%
“…106 Sleep disorders, such as problematic sleep onset, maintenance, duration, quality, and daytime sleepiness, are consistently reported. 5,53,57,107,108 However, sleep studies in adults have shown little differences in sleep characteristics among POTS patients and controls. 109 -112 Cognitive symptoms or brain fog, which is described as having difficulty with attention, concentration, and memory, are commonly reported in POTS.…”
Section: Immune Mechanismsmentioning
confidence: 99%
“…In one study, 28.9% of patients excreted less than 100 mEqIL j1 of sodium in 24 h (3,45) and a large subgroup experienced low plasma, total blood volumes, and red cells (3,33,42,44), illustrating a compensatory physiologic mechanism that differs from chronic dehydration in which the body retains sodium, thus retaining water, to prevent further dehydration. After saline loading, the affected patient's urinary sodium increased and symptoms improved (23). Angiotensinconverting enzyme 2 activity has been shown to be reduced in these patients with inappropriately high plasma angiotensin II levels (3,42).…”
Section: Discussionmentioning
confidence: 99%
“…Potential risk factors for POTS in children and adolescents include a faster supine heart rate, less water intake, and shorter sleeping hours. 7 Currently, there are no clinical trial-or guidelines-established treatments for POTS or class I recommendations for its therapy. Although one study has indicated that one treatment may yield better outcomes over another, 8 another suggested a multidisciplinary approach that includes both conservative and nonpharmacologic measures may be best.…”
Section: Discussionmentioning
confidence: 99%